From Item Development to Analysis: The Development of a Computerised Entrance Placement Test Using a VLE - Soproni, Zsuzsanna (Working Papers in Language Pedagogy, 2020)
This paper reports using a virtual learning environment (VLE) for English language reading and writing competence testing as part of a higher education entrance placement test for a business college. The suitability of the VLE for computer-based testing, as well as the effect of its mode of delivery, including the perceptions of test-takers are discussed through the findings of quantitative and qualitative action research investigations. More specifically, within suitability, the transferability of specific tasks, security issues, user-friendliness and data processing are examined. It was found that prior computer-based test-taking experience is not an unfair advantage for applicants, but sample tests need to be made accessible to cater for the time needs of applicants with no prior computer-based experience. The VLE has proved to be a suitable platform for the purpose, in terms of test design, security, transferability and data processing, but only with the help of database engineers was some of the data retrievable. Thus, the paper seeks to emphasise the need for collaboration between information technology personnel and language testing professionals.